Effect of repeated electrical breakdowns on mineral and natural ester insulating oils - Sharin Ab Ghani; Mohd Shahril Ahmad Khiar; Imran Sutan Chairul; Muhammad Imran Zamir (Bulletin of Electrical Engineering and Informatics, 2021)
Transformer insulating oils are exposed to repeated electrical discharge or breakdowns inside power transformers. Durability tests are conducted to analyze the ability of oil to resist decomposition due to such high electrical stresses. With the increasing demand for alternative insulating oils for oil-immersed transformers, it is worthy to compare the performance of different types of insulating oils (conventional mineral-based insulating oil and natural ester-based insulating oil) under repeated electrical breakdown. In this paper, the AC breakdown voltage of different mineral-based and natural ester-based insulating oils is reported. Durability tests were conducted based on the AC breakdown voltage behavior of insulating oils after 50 electrical breakdown shots. The AC breakdown voltage of each insulating oil sample was assessed according to the ASTM D1816 standard test method. Based on the results, it can be concluded that the dissimilarity in chemical composition of the insulating oils has a significant effect on the AC breakdown voltage behavior of these oils under repeated electrical breakdowns.